معيقات تطبيق حصة التربية البدنية والرياضية في الطور الابتدائي - سعون; جهل, محمد الصديق (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
وتهدف الدراسة التي بين أيدينا إلى محاولة معرفة معيقات تطبيق حصة التربية البدنية والرياضية في الطور الابتدائي، ولأجل ذلك اتبعنا المنهج الوصفي، حيث تكونت عينة الدراسة من 30استاذ واستاذة لمادة التربية البدنية والرياضية في الطور الابتدائي بولاية مستغانم، واستعملنا الاستبيان كأداة للدراسة، واستخدمنا لتحويل البيانات الى نتائج إحصائية معامل (الصدق، الثبات، معامل الارتباط البسيط لبيرسون)، وجاءت أهم نتائج الدراسة ان الوقت المخصص لأساتذة المادة في حصة التربية البدنية والرياضية لا يكفيهم لتطوير الجانب الحركي للتلاميذ، وان الوقت المخصص للتلاميذ للخروج من القسم وتغيير ملابسهم غير كاف للذهاب إلى حصة التربية البدنية في الوقت المحدد، اما اهم الاقتراحات والتوصيات فتمثلت بداية بضرورة تكوين مفتشين لمادة التربية البدنية في الطور الابتدائي، على الوزارة الوصية توفير الإمكانيات والوسائل اللازمة داخل المؤسسات التربوية وذلك حتى نمكن المربي من القيام بمهامه على أحسن وجه. // // // // // The study at hand aims to try to find out the obstacles to implementing the physical education and sports class in the primary stage. To do this, we followed the descriptive approach, as the study sample consisted of 30 male and female professors of physical education and sports in the primary level in the state of Mostaganem. We used the questionnaire as a tool for the study, and used it to transform the data into Statistical results of the coefficient (validity, reliability, Pearson's simple correlation coefficient). The most important results of the study were that the time allocated to the subject teachers in the physical education and sports class is not enough for them to develop the motor side of the students, and that the time allocated for the students to leave the classroom and change their clothes is not enough to go to the education class. Physical education at the specified time. As for the most important suggestions and recommendations, the beginning was the necessity of forming inspectors for physical education in the primary stage. The Ministry must provide the necessary capabilities and means within educational institutions in order to enable the educator to carry out his duties in the best possible way.
LEPS-2024-21
Keywords: حصة التربية البدنية والرياضية- الطور الابتدائي - معيقات // // physical education and sports class - primary stag